2021
DOI: 10.3390/foods10020480
|View full text |Cite
|
Sign up to set email alerts
|

Dishes Adapted to Dysphagia: Sensory Characteristics and Their Relationship to Hedonic Acceptance

Abstract: Dishes whose texture has been modified for dysphagia undergo changes in other sensory characteristics as well. Therefore, it is necessary to identify these characteristics in adapted dishes and their relationship to hedonic acceptance. In the present work, the sensory characteristics of five dishes adapted to dysphagia associated with cerebral palsy were investigated using the check-all-that-apply method. A hedonic evaluation with a panel of non-dysphagic judges was performed to relate the degree of acceptance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…This is especially necessary as dysphagia awareness increases globally, and systems such as the IDDSI are suggested to modify regional foods and drinks that may not be comparable to how the system was first designed [ 29 ]. The addition of rheological and sensory analysis of food will likely provide insights into how and why certain textures are suited to those experiencing dysphagia [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is especially necessary as dysphagia awareness increases globally, and systems such as the IDDSI are suggested to modify regional foods and drinks that may not be comparable to how the system was first designed [ 29 ]. The addition of rheological and sensory analysis of food will likely provide insights into how and why certain textures are suited to those experiencing dysphagia [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the included publications were based on descriptive sensory analysis, highlighting QDA ® (Baert et al., 2021; Mann & Wong, 1996; Wendin et al., 2010). Other methods such as Free Choice Profiling (Baert et al., 2021), Projective Mapping (Field et al., 2017), and CATA (Merino et al., 2021) were used to select descriptors for a posterior descriptive analysis or to characterize the TMFs. Also, other methods such as the Temporal Dominance Sensations (TDS) and Temporal Check‐All‐That‐Apply (TCATA) (Sharma & Duizer, 2019) begin to be used for the characterization of food for dysphagia during the complete swallowing process.…”
Section: Resultsmentioning
confidence: 99%
“…These authors concluded that products suitable for dysphagia should have low firmness intensities (between 1 and 2 in a 1‐ to 5‐point scale), medium‐high in cohesiveness (3–4.5/5), high fluidity (4–5/5), and very low residue and stickiness (1–1.5/5). The five TMFs were also evaluated with a panel of untrained assessors using the CATA method (Merino et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ohmic heating was utilized to improve and preserve the main properties of purées. Antioxidant activity has also increased with ohmic heating, up to 58% compared to the control sample [ 137 ]. The study shows the potential of this treatment for ready-to-eat courgettes as food that can be developed for dysphagic patients.…”
Section: Modifying Texture For Dysphagic Patientsmentioning
confidence: 99%